Meningkatkan Faktor Perolehan Lapangan Marginal dengan Metode Injeksi Air, Sebuah Studi Simulasi Reservoar - Edy Slameto (Pusat Survei Geologi, 2006)
The development of marginal fields is becoming a more important alternative method, due to the fact that big and profitable new fields are more difficult to be discovered. A marginal field which is situated in the Western Sunda Basin, here is called as Field X, has big enough reserves in which specific fluid property interest has to be concerned. Its OGIP: 7.675 BSCF and OOIP: 129.058 MMSTB (based on PSC source). According to the trap existing in the field, its drive mechanism is Gas Cap Drive and Water Drive. In order to increase the recovery factor of this field, Enhanced Oil Recovery (EOR) using water injection method has been carried out. Reservoir simulation performed with water injection project to this field could increase the cumulative oil production into 17.160 MMSTB with 13.29 % composite recovery factor for 30 years.Â Keywords : waterflood, reservoir simulation, marginal, Sunda Basin